Implementasi Karakter Keislaman Dalam Mengatasi Paham Radikalisme di Kalangan Mahasiswa - Al Fitri, Rafli; Nurwahid, Muhammad Agus Setiawan (Program Studi Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Islam 45, 2024)
There are many religious activities at the university, both general and religious. Radicalism comes from the word radical which means massive or comprehensive, hard, sturdy, advanced and sharp (in thinking). Radical is usually defined as a political consensus of government that calls for radical change or reform as the way forward. This research uses a type of study or library research. This research aims to establish Islamic character in overcoming radicalism. The concept of radicalism itself is sometimes defined differently within interest groups. In this case, universities play an important role in efforts to instill the values ​​of moderation through education that includes the whole community, has a sense of tolerance, respects differences and spreads peace, and has the effect of reasonable understanding to benefit others, not to deny, doubt or even underestimating the stigma of takfiri, committing disgraceful acts and using religion as a basis to justify their actions.